2017
DOI: 10.22159/ijcpr.2017v9i4.20981
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity and Biogenic Synthesis of Selenium Nanoparticles Using the Leaf Extract of Aloe Vera

Abstract: Objective: The objective of this present study were to the biogenic synthesis of selenium nanoparticles using Aloe vera extract and check it's antioxidant potential by ABTS, DPPH and FRAP assays. Methods:In this study we investigated the clove of Aloe vera, which is used for the synthesis of selenium nanoparticles were characterized by using UV-Visible (UV-VIS) spectrophotometer, Transmission electron microscopy (TEM), Fourier transform spectroscopy (FTIR) and Energy dispersive XRay spectroscopy (EDAX) and ABT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 10 publications
3
19
0
Order By: Relevance
“…The reduction of selenium ions into SeNPs induced by propolis extracts was confirmed by the conversion of color from light brown to reddish orange after the addition of acidic sodium selenite solution which is the most significant property of nanoparticles. Result is in accordance with the previous report [39] on synthesis of SeNPs mediated by aqueous extract of Aloe vera leaf. Present results also correlates with UV-visible spectra of SeNPs biosynthesised from the aqueous extract of orange peel and Petroselinum crispum leaf showed the peak at 265.5-270 nm respectively [40,41].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The reduction of selenium ions into SeNPs induced by propolis extracts was confirmed by the conversion of color from light brown to reddish orange after the addition of acidic sodium selenite solution which is the most significant property of nanoparticles. Result is in accordance with the previous report [39] on synthesis of SeNPs mediated by aqueous extract of Aloe vera leaf. Present results also correlates with UV-visible spectra of SeNPs biosynthesised from the aqueous extract of orange peel and Petroselinum crispum leaf showed the peak at 265.5-270 nm respectively [40,41].…”
Section: Discussionsupporting
confidence: 93%
“…However, the propolis samples collected from Karnataka exhibited an effective radical inhibition in all the assays compared to other states. SeNPs are less toxic form of selenium, has been proved to have antioxidant activity and is being used as chemopreventive agent in cancer treatment [39]. Nanoparticles are endorsed as sustainable antimicrobial agents having remarkable perspective to resolve the microbial multidrug resistance problem [51,52] and microbial biofilm formation [12,53].…”
Section: Discussionmentioning
confidence: 99%
“…The results at the end of the storage period indicated that the CTR and the AVG-treatment lost 4.98% and 2.92%, respectively, while the AVG/HPMC and AVG/LEO treatments minimized weight loss (1.50% and 1.56%, respectively) by maintaining the water content in fresh-cut apple. In fact, this weight loss is probably caused by the water evaporation on the fruit surface and is a leading cause of quality loss, such as shriveling of the surface and decreased juiciness [6,42]. Nonetheless, there are not many studies available in the literature concerning the mixing of HPMC with Aloe vera gel and lemon essential oil to form edible or biodegradable films or packages, to compare with our data.…”
Section: Weight Lossmentioning
confidence: 80%
“…The ammonia formed during this distillation was collected in a boric acid solution and determined through titrimetric dosage. The value of ammoniacal nitrogen was multiplied by 6.25 [42].…”
Section: Proximate Compositionmentioning
confidence: 99%
“…According to the findings of a study conducted by Shubharani et al, there is a significant relationship between the antioxidant activity of SeNPs and increasing its concentration (24). In addition, in another study performed by Vyas et al, the antioxidant activity of garlic (Allium sativum) extract was evaluated, and the inhibition effect of SeNPs in a 600-µM concentration was 67%, depending on the dose of SeNPs (30).…”
Section: Discussionmentioning
confidence: 99%